Ottomans, Hungarians, and Habsburgs in Central Europe : The Military Confines in the Era of Ottoman Conquest - David, Geza,; Fodor, Pál, (Brill Book Archive Part 1, ISBN: 9789004472495., 2000)
The Central European military frontier in the fifteenth-seventeenth centuries hides a treasure of military history information. This collective volume provides a fascinating overview to scholars and students interested in the paradigms of the history of frontiers, of imperial structures, and of early modern state finances. The first part of the book examines the birth and development of the Hungarian and Habsburg defence systems from their origins until their dissolution in the early eighteenth century. The second part focuses on the Ottoman military establishment in Hungary. Special emphasis has been put throughout on administration, finance, manpower problems, and aspects of the military revolution in the marches. The book is unique in its complex and comparative approach; no similar effort has yet been made concerning other areas of the Ottoman Empire.